Freeze–thaw hydrogel fabrication method: basic principles, synthesis parameters, properties, and biomedical applications - William Xaveriano Waresindo; Halida Rahmi Luthfianti; Aan Priyanto; Dian Ahmad Hapidin; Dhewa Edikresnha; Akfiny Hasdi Aimon; Tri Suciati; Khairurrijal Khairurrijal (Materials Research Express, 2023)
Hydrogel is being broadly studied due to their tremendous properties, such as swelling behavior and biocompatibility. Numerous review articles have discussed hydrogel polymer types, hydrogel synthesis methods, hydrogel properties, and hydrogel applications. Hydrogel can be synthesized by physical and chemical cross-linking methods. One type of the physical cross-linking method is freeze-thaw (F–T), which works based on the crystallization process of the precursor solution to form a physical cross-link. To date, there has been no review paper which discusses the F–T technique specifically and comprehensively. Most of the previous review articles that exposed the hydrogel synthesis method usually mentioned the F–T process as a small part of the physical cross-linking method. This review attempts to discuss the F–T hydrogel specifically and comprehensively. In more detail, this review covers the basic principles of hydrogel formation in an F–T way, the parameters that influence hydrogel formation, the properties of the hydrogel, and its application in the biomedical field.